Down-conversion Ce-doped TiO2 nanorod arrays and commercial available carbon based perovskite solar cells: Improved performance and UV photostability. (27th January 2021) - Chen, Koucheng; Zhang, Heng; Tong, Hui; Wang, Ling; Tao, Lu; Wang, Ke; Zhang, Yinxi; Zhou, Xingfu
Abstract: Ce-doped TiO2 nanorod arrays as the mesoporous supporting layer and TiO2 compacted electron blocking layer was simultaneously fabricated by one-pot hydrothermal method. Ce-doped TiO2 nanorod was utilized as down-conversion luminescence centers and commercial available carbon was used in hole-transport-free perovskite solar cells. SEM indicated that the doping of Ce reduced the diameter of TiO2 nanorods. XRD and EDS spectra demonstrate the successful incorporation of Ce ions. UV–Vis absorption spectra and PL emission spectra show that the down-conversion center Ce 4+ can effectively utilize ultraviolet light and extend the absorption into the ultraviolet region. The carbon-based device using the optimized Ce doping concentration achieved power conversion efficiency (PCE) of 10.1%, which was 24.6% higher than that of undoped device. Ce doping changes the band gap of TiO2 and the Fermi energy level, and thus improve the open circuit voltage. The open circuit voltage decay curve show that Ce-doped TiO2 prolongs electron lifetime. EIS analysis hints that more carriers are generated. The UV stability has also been significantly improved., PCE of the optimized Ce-doped device still retains 90% of the initial value, however, the undoped device decreases to 55% of the initial value under light irradiation at ambient atmosphere for 12 h. Highlights: Ce dopnant change TiO2 fermi energy level and improve the open circuit voltage. Ce-doped device get 24.6% increase in conversion efficiency. PCE of Ce-doped device retains 90% of the initial value.